Validated multiclass targeted determination of antibiotics in fish with high performance liquid chromatography–benchtop quadrupole orbitrap hybrid mass spectrometry. (30th August 2018) - Chiesa, Luca; Panseri, Sara; Pasquale, Elisa; Malandra, Renato; Pavlovic, Radmila; Arioli, Francesco
Highlights: Full scan-data dependent acquisition mode met legal identification requirements. High resolution mass spectra of 25 antibiotics were the main identifiers. The method was applicable in fish from diverse origin and cultivation methods. Sample analysis revealed presence of some antibiotics, but these were under MRLs. Abstract: High performance liquid chromatography, coupled with a benchtop Q-Exactive Orbitrap high-resolution mass spectrometer, was successfully applied for the determination of 24 target antibiotics (selected beta-lactams, tetracyclines, fluoroquinolones, sulfonamids, phenicols, macrolides, cephalosporins, lincosamides, diaminopyrimidine) in fish matrices. The Q-Exactive parameters were carefully studied to accomplish the best compromise between a suitable scan speed and selectivity, considering the restrictions associated with generic sample preparation methodology. Retention time, an exact mass with tolerance of 2 ppm and data-dependent MS 2 spectra were the main identifiers. The method was validated through specificity, linearity, recovery, intra- and inter-day repeatability, decision limit (CCα) and detection capability (CCβ), according to 2002/657/EC. The values of CCα and CCβ ranged from 29.2 to 36.8 and 32.5 to 48.9, respectively, while overall recovery ranged from 91.1 to 105.6%. Fifty fish samples were analysed, showing the sporadic incidence of enrofloxacin, chlortetracycline, oxytetracycline, amoxicillin and trimethoprim, albeit below the maximum residual levels.